Petrogenetic links between lepidolite-subtype aplite-pegmatite, aplite veins and associated granites at Segura (central Portugal) - Antunes, Isabel Margarida Horta Ribeiro (2014)
In the Segura area, Variscan S-type granites, aplite veins and lepidolite-subtype granitic aplite-pegmatite veins intruded the Cambrian schist-metagraywacke complex. The granites are syn D3. Aplite veins also intruded the granites. Two-mica granite and muscovite granite have similar ages of 311.0 ± 0.5 Ma and 312.9 ± 2.0 Ma but are not genetically related, as indicated by their geochemical characteristics and (87Sr/86Sr)311 values. They correspond to distinct pulses of magma derived by partial melting of heterogeneous metapelitic rocks. Major and trace elements suggest fractionation trends for: (a) muscovite granite and aplite veins; (b) two-mica granite and lepidolite-subtype aplite-pegmatite veins, but with a gap in most of these trends. Least square analysis for major elements, and modeling of trace elements, indicate that the aplite veins were derived from the muscovite granite magma by fractional crystallization of quartz, plagioclase, K-feldspar and ilmenite. This is supported by the similar (87Sr/86Sr)311 and δ18O values and the behavior of P2O5 in K-feldspar and albite. The decrease in (87Sr/86Sr)311 and strong increase (1.6‰) in δ18O from two-mica granite to lepidolite-subtype aplite-pegmatite veins, and the behaviors of Ca, Mn and F of hydroxylapatite indicate that these veins are not related to the two-mica granite. The occurrence of amblygonite–montebrasite, lepidolite, cassiterite, columbite-(Fe), columbite-(Mn) and microlite suggests that lepidolite-subtype granitic aplite-pegmatite veins are highly differentiated. Montebrasite shows a heterogeneous Na distribution and secondary lacroixite was identified in some montebrasite areas enriched in Na. Unusual Mn > Fe cassiterite is zoned, with the alternating darker zones being strongly pleochroic, oscillatory zoned, and containing more Nb and Ta than the lighter zones. Inclusions of muscovite, apatite, tapiolite-(Fe), ixiolite and microlite are present both in lighter and darker zones of cassiterite. It shows exsolutions of columbite-(Fe), columbite-(Mn,Fe) and columbite-(Mn), particularly in darker zones.